Analisis Perbandingan Model Z Altman dan Model the Grover dalam Mengukur Kesehatan Perusahaan Food and Beverages di Bursa Efek Indonesia - Yuni Arti; Debbi Chyntia Ovami (Jurnal Multidisiplin Madani, 2022)
This study aims to determine and analyze the comparison of the Altman Z-Score model and the Grover model in predicting the health level of food and beverages companies on the Indonesia Stock Exchange for the 2018-2020 period. The type of research used is quantitative analysis. The data used in this study are financial reports published through the IDX. The sampling technique used purposive sampling technique in order to obtain 14 companies that were used as research samples. The data analysis technique used the independent sample t-test and the level of accuracy test. The conclusion of this study shows that there is a significant difference between the Altman Z-Score model and also the Grover model in measuring company health. The most accurate prediction model was achieved by the Grover model with an accuracy percentage of 100% and the Altman Z-Score model with an accuracy rate of 90.48%.